A method for rapidly densifying solid oxide electrolyte for lithium-ion batteries
Through the power-on-conducting substrate to generate Joule heat and segmented sintering technology, the problem of long sintering time and low efficiency of solid electrolytes of lithium-ion batteries is solved, and the rapid preparation of oxide solid electrolyte sheets with high ionic conductivity and density is achieved, reducing energy consumption and cost.
Patent Information
- Application Number
- CN202410731922.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The safety and energy density of traditional liquid electrolytes in lithium-ion batteries are limited, and the sintering process of oxide solid electrolytes takes a long time, resulting in low preparation efficiency, high energy consumption and increased cost.
The conductive substrate is powered on to generate Joule heat. Combined with the segmented sintering technology, the first section is initially densified and sintered to reduce temperature differences and thermal expansion inhomogeneity, and the second section densified and sintered further reduces voids at higher temperatures, improving density and ionic conductivity.
The sintering time of the oxide solid electrolyte sheet is shortened to within 40s, the density and ionic conductivity of the electrolyte sheet are improved, and the preparation energy consumption and cost are reduced.
Smart Images

Figure CN118724582B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material solid electrolyte ceramic sheets and relates to a method for rapidly densifying a lithium ion battery oxide solid electrolyte. Background Art
[0002] The widespread use of lithium-ion batteries in our daily lives has improved people's quality of life. However, traditional liquid electrolytes have high safety risks and their energy density is greatly limited. Compared with traditional liquid electrolytes, solid electrolytes have the advantages of high safety, high energy density, wide electrochemical window, and high ion conductivity. They effectively solve the problems of lithium-ion battery safety and limited energy density, and have received widespread attention, becoming a new generation of battery technology with great potential.
[0003] Solid-state electrolytes can be mainly divided into three types: oxide solid electrolytes, sulfide solid electrolytes, and polymer solid electrolytes. Among them, oxide solid electrolytes have broad development prospects and application potential due to their good environmental stability, wide source of raw materials, low manufacturing cost, and high ionic conductivity.
[0004] At present, in the process of preparing oxide solid electrolytes, sintering is mainly carried out by pressureless sintering technology, hot pressing sintering technology, and spark plasma sintering technology. However, the pressureless sintering technology has a slow heating rate, which is easy to cause problems such as excessive grain size and volatilization of lithium elements during the sintering process, resulting in a decrease in the ionic conductivity of the oxide solid electrolyte sheet. At the same time, the relatively long sintering time not only makes the preparation of the oxide solid electrolyte take a long time and has low efficiency, but also consumes more energy and has a large energy consumption; hot pressing sintering and spark plasma sintering have higher temperatures and better thermal insulation effects than pressureless sintering, but they also require a relatively long sintering time, and the sintering process requires pressure to promote the densification of the material, which increases the energy consumption and cost of preparation. At the same time, during the sintering process, the oxide solid electrolyte will be contaminated by the graphite mold, and the sintered solid electrolyte needs to be decontaminated, which further increases the complexity of preparation and leads to an increase in energy consumption and cost.
[0005] Therefore, it is necessary to provide a method for rapidly densifying the preparation of lithium-ion battery oxide solid electrolytes, effectively shorten the preparation time, and prepare oxide solid electrolyte sheets with high ionic conductivity in a shorter time, thereby avoiding the influence of long-term preparation on electrolyte performance and reducing energy consumption and preparation costs. Summary of the invention
[0006] In order to overcome the problems in the background technology, the present invention uses a conductive substrate to generate Joule heat by energizing it, combined with a segmented sintering technology, the first stage of preliminary densification sintering, reduces the temperature difference and thermal expansion non-uniformity inside the material, thereby reducing the generation of thermal stress, ensuring that the electrolyte sheet will not crack or deform during further temperature increase sintering; the second stage of densification sintering, at a higher temperature, further reduces the gap, improves the density and ionic conductivity of the electrolyte sheet. By adopting this technology, a flat oxide solid electrolyte with high ionic conductivity can be obtained, and the sintering time can be shortened to less than 40s.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] In one aspect, the present invention provides a method for rapidly densifying a solid oxide electrolyte for lithium-ion batteries, the method comprising the following steps:
[0009] (1) The oxide solid electrolyte powder is pressed into a sheet to prepare an electrolyte green body.
[0010] (2) placing the green body between conductive substrates, and under atmosphere protection conditions, energizing the conductive substrates so that the conductive substrates generate Joule heat under the action of the current, and sintering the green body. The temperature of the conductive substrates is controlled by the magnitude of the current passing through the conductive substrates. The sintering process is divided into two stages. The sintering temperature of the first stage is 400-700° C., and the constant temperature time is 3-30 seconds; the sintering temperature of the second stage is 900-1200° C., and the constant temperature time is 1-10 seconds. After sintering, an oxide solid electrolyte sheet is obtained.
[0011] Preferably, the oxide solid electrolyte powder comprises one of NASICON type, garnet type, perovskite type and LISICON type.
[0012] Preferably, in step (1), the tableting pressure is 2 to 8 MPa, and the holding time is 1 to 3 min.
[0013] Preferably, in step (1), the oxide solid electrolyte green body is a circular sheet with a diameter of 12 to 18 mm and a thickness of 0.5 to 2 mm, and the amount of oxide solid electrolyte powder used is 0.15 to 0.5 g.
[0014] Preferably, the conductive substrate is a rectangular structure, and the width of the conductive substrate is 1 to 3 times the diameter of the oxide solid electrolyte green body.
[0015] Preferably, in step (2), sintering is performed in a protective atmosphere or under vacuum conditions, and the protective atmosphere is one of air, oxygen and argon.
[0016] Preferably, in step (2), the prepared oxide solid electrolyte sheet has a structure selected from the group consisting of NASICON type, garnet type, perovskite type, and LISICON type, and has an ionic conductivity greater than or equal to 2.0×10 -4 S / cm, density is greater than or equal to 97%, and the electrochemical stability window is 0-6V.
[0017] Preferably, the conductive substrate is one of nickel foil, copper foil, aluminum foil, carbon cloth, carbon felt, carbon fiber, and graphite crucible.
[0018] On the other hand, the present invention provides a lithium-ion battery oxide solid electrolyte sheet, which is prepared by the above method, and the prepared oxide solid electrolyte sheet has one of the structures of NASICON type, garnet type, perovskite type, and LISICON type.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention uses Joule heat generated by electrifying a conductive substrate as a heat source to rapidly sinter the oxide electrolyte green body, which can greatly shorten the sintering time. The total sintering time of the two stages does not exceed 40 seconds.
[0021] (2) The present invention combines the staged sintering technology. The first stage is the preliminary densification sintering to reduce the temperature difference and thermal expansion non-uniformity inside the material, thereby reducing the generation of thermal stress. The second stage is the densification sintering at a higher temperature to further reduce the porosity and improve the density of the electrolyte sheet. Based on a shorter sintering time, a flat and dense LATP oxide solid electrolyte sheet can be prepared while maintaining a higher ionic conductivity and a wider electrochemical window.
[0022] (3) The preparation method of the present invention is simple, easy to operate, has a short preparation time, high efficiency, low equipment requirements, and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are X-ray diffraction (XRD) diagrams of the LATP oxide solid electrolyte sheets prepared in Example 1, Comparative Example 1, and Example 5 of the present invention.
[0024] Figure 2 This is a scanning electron microscope (SEM) image of the LATP oxide solid electrolyte sheet prepared in Example 1 of the present invention.
[0025] Figure 3 This is a scanning electron microscope (SEM) image of the LATP oxide solid electrolyte sheet prepared in Example 5 of the present invention.
[0026] Figure 4This is a scanning electron microscope (SEM) image of the LATP oxide solid electrolyte sheet prepared in Comparative Example 1 of the present invention.
[0027] Figure 5 This is a room temperature impedance spectroscopy (EIS) graph of the LATP oxide solid electrolyte sheet prepared in Example 1 of the present invention.
[0028] Figure 6 This is a room temperature impedance spectroscopy (EIS) graph of the LATP oxide solid electrolyte sheet prepared in Example 5 of the present invention.
[0029] Figure 7 This is a room temperature impedance spectroscopy (EIS) graph of the LATP oxide solid electrolyte sheet prepared in Comparative Example 1 of the present invention.
[0030] Figure 8 This is the activation energy diagram of the LATP oxide solid electrolyte sheet prepared in Example 1 of the present invention.
[0031] Fig. 9 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0033] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure reagents for the experiments.
[0034] In the present invention, examples 1, 2 and 3 are used to prepare LATP green body Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder was prepared by the following method:
[0035] Q1: Li 1.4 Al 0.4 Ti 1.6 The (PO4)3 solid electrolyte powder raw material was mixed with anhydrous ethanol at a solid-liquid ratio of 1 g:2 mL, and placed in a zirconia ball mill to mix evenly. The wet milling speed was 1000 r / min and the wet milling time was 2 h to obtain a mixed slurry.
[0036] Q2: Use a vacuum drying oven to dry the mixed slurry obtained in step Q1 at a drying temperature of 80° C. for 4 hours, and sieve and separate to obtain the treated LATP solid electrolyte powder.
[0037] Example 1
[0038] In this embodiment, LATP oxide solid electrolyte is prepared by the following method:
[0039] (1) 0.25 g of the treated LATP solid electrolyte powder prepared above was taken and maintained at 4 MPa for 2 min, and cold pressed to obtain a circular sheet with a diameter of 16 mm and a thickness of 0.8 mm, which is the LATP green body.
[0040] (2) The LATP green body is placed at the center between two rectangular carbon felts of the same size, and the width of the rectangular carbon felt is 25 mm. Under air atmosphere conditions, the carbon felt is energized to generate Joule heat under the action of the current, and the LATP green body is sintered in stages. The sintering temperature of the first stage is 500°C, and the constant temperature time is 20 s; the sintering temperature of the second stage is 900°C, and the constant temperature time is 2 s. After sintering, the LATP oxide solid electrolyte sheet is obtained.
[0041] The LATP oxide solid electrolyte sheet prepared in this example was characterized and analyzed, and its XRD diffraction pattern is as follows: Figure 1 As shown in the SEM images Figure 2 As shown, the EIS spectrum is Figure 5 As shown in the activation energy diagram, Figure 8 shown.
[0042] pass Figure 1 It can be seen that the LATP oxide solid electrolyte sheet prepared in this example matches the standard card and has no obvious impurity peaks, indicating that the prepared LATP oxide solid electrolyte sheet is LATP with high purity.
[0043] pass Figure 2 It can be seen that the LATP oxide solid electrolyte sheet prepared in this embodiment has uniform grain size, high density, and no obvious voids, indicating that the sample has good crystallinity and density, which is beneficial to improving its ion conductivity and cycle stability.
[0044] based on Figure 5 As a result, after fitting and calculation, the ionic conductivity of the LATP oxide solid electrolyte sheet prepared in this embodiment is 2.99×10 -4 S / cm.
[0045] based on Figure 8 As a result, after fitting and calculation, it was found that the activation energy of the LATP oxide solid electrolyte sheet prepared in this embodiment was 0.324 eV.
[0046] Example 2
[0047] In this embodiment, LATP oxide solid electrolyte is prepared by the following method:
[0048] (1) 0.28 g of the treated LATP solid electrolyte powder prepared above was taken and maintained at 4 MPa for 2 min, and cold pressed to obtain a circular sheet with a diameter of 18 mm and a thickness of 0.8 mm, which is the LATP green body.
[0049] (2) The LATP green body is placed at the center between two rectangular carbon felts of the same size so that the LATP green body is completely wrapped by the carbon felt. Under air atmosphere conditions, the carbon felt is energized so that the carbon cloth generates Joule heat under the action of the current. The LATP green body is sintered in stages. The sintering temperature of the first stage is 700°C and the constant temperature time is 3s; the sintering temperature of the second stage is 1200°C and the constant temperature time is 2s. After sintering, the LATP oxide solid electrolyte sheet is obtained.
[0050] The structure and performance of the LATP oxide solid electrolyte sheet prepared in this example are similar to those in Example 1.
[0051] In the present invention, Example 4 and Example 5 are used to prepare Li 2+ LLZTO green body. 6.4 Ln3Z 1.4 Ta 0.6 O 12 The solid electrolyte powder is prepared by the following method:
[0052] Q1: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The solid electrolyte powder raw material and isopropanol were mixed in a solid-liquid ratio of 1 g:2 mL, placed in a zirconia ball mill and mixed evenly, the wet milling speed was 1000 r / min, the wet milling time was 2 h, and a mixed slurry was obtained.
[0053] Q2: The mixed slurry obtained in step Q1 is dried in a vacuum drying oven at a temperature of 80° C. for 4 h, and the treated LLZTO solid electrolyte powder is separated by sieving.
[0054] Example 3
[0055] (1) 0.45 g of the treated LLZTO solid electrolyte powder prepared above was taken and maintained at 8 MPa for 1 min, and cold pressed to obtain a circular sheet with a diameter of 16 mm and a thickness of 0.8 mm, which is the LLZTO green body.
[0056] (2) The LLZTO green body is placed at the center between two rectangular carbon felts of the same size so that the LLZTO green body is completely wrapped by the carbon felt. Under oxygen atmosphere conditions, the carbon felt is energized so that the carbon cloth generates Joule heat under the action of the current. The LLZTO green body is sintered in stages. The sintering temperature of the first stage is 600°C and the constant temperature time is 10s; the sintering temperature of the second stage is 1200°C and the constant temperature time is 5s. After sintering, the LLZTO oxide solid electrolyte sheet is obtained.
[0057] The LLZTO oxide solid electrolyte sheet prepared in this embodiment was characterized and analyzed, and its XRD diffraction pattern is as follows: Figure 2 As shown in the SEM images Figure 4 shown.
[0058] pass Figure 2 It can be seen that the LLZTO oxide solid electrolyte sheet crystal phase prepared in this embodiment matches the standard card, and there is no obvious impurity peak, indicating that the prepared LLZTO oxide solid electrolyte sheet is a garnet-type electrolyte sheet with high purity.
[0059] pass Figure 4 It can be seen that the LLZTO oxide solid electrolyte sheet prepared in this embodiment has uniform grains without obvious gaps and high density, which means that the sample has good crystallinity and density, which is beneficial to improving its ion conductivity and cycle stability.
[0060] Example 4
[0061] This embodiment adopts the same method as that of embodiment 4 to prepare LLZTO oxide solid electrolyte, except that: in this embodiment, the first stage sintering temperature is 500° C., and the constant temperature time is 30 s; the second stage sintering temperature is 1100° C., and the constant temperature time is 5 s.
[0062] The structure and performance of the LLZTO oxide solid electrolyte sheet prepared in this example are similar to those in Example 4.
[0063] Example 5
[0064] In this embodiment, LATP oxide solid electrolyte is prepared by the following method:
[0065] (1) 0.25 g of the treated LATP solid electrolyte powder prepared above was taken and maintained at 4 MPa for 2 min, and cold pressed to obtain a circular sheet with a diameter of 16 mm and a thickness of 0.8 mm, which is the LATP green body.
[0066] (2) Clamping the LATP green body, the LATP green body is placed at the center between two rectangular carbon cloths of the same size, so that the LATP green body is completely wrapped by the carbon cloth. Under argon atmosphere, the carbon cloth is energized to generate Joule heat under the action of the current, and the LATP green body is sintered in stages. The sintering temperature of the first stage is 500°C, and the constant temperature time is 20s; the sintering temperature of the second stage is 900°C, and the constant temperature time is 2s. After sintering, the LATP oxide solid electrolyte sheet is obtained.
[0067] The LATP oxide solid electrolyte sheet prepared in this example was characterized and analyzed, and its XRD diffraction pattern is as follows: Figure 1 As shown in the SEM images Figure 3 As shown, the EIS spectrum is Figure 6 shown.
[0068] pass Figure 1 It can be seen that when the LATP oxide solid electrolyte sheet prepared in this embodiment is compared with the standard card, TiP2O7 and Li4P2O7 impurities are generated.
[0069] pass Figure 3 It can be seen that the LATP oxide solid electrolyte sheet prepared in this embodiment has high grain density and no obvious voids, but compared with Example 1, some grains are uneven in size.
[0070] based on Figure 6 After fitting and calculation, the ionic conductivity of the LATP oxide solid electrolyte sheet prepared in this embodiment is 3.71×10 -6 S / cm is because when argon is used as the protective atmosphere, no oxide layer is formed to stabilize lithium like oxygen, resulting in a large amount of volatilization of lithium, which greatly reduces its ionic conductivity.
[0071] It can be seen from Examples 1-5 that:
[0072] (1) Sintering can be performed under oxygen, air or argon atmosphere conditions because the sintering process of oxide solid electrolytes is relatively stable and is more adaptable to changes in sintering conditions under oxygen and air atmospheres.
[0073] (2) The conductive substrate has good conductivity, chemical stability and high temperature resistance; during the sintering process, the conductive substrate can provide support and conductive functions, which helps to maintain the shape of the oxide solid electrolyte.
[0074] (3) Under a certain range of sintering temperature and sintering time conditions, changes in sintering temperature and sintering time do not have a significant effect on the performance of the prepared oxide solid electrolyte sheet. This is because LATP has a high crystallization temperature and a stable structure, and changes in sintering time do not have a significant effect on its performance. Therefore, the rapid sintering method has a certain stability.
[0075] Comparative Example 1
[0076] This comparative example adopts the same method as Example 1 to prepare the LATP oxide solid electrolyte sheet, except that: in this comparative example, a muffle furnace is used to sinter the LATP green body, and the sintering conditions are: heating to 900°C at a rate of 3°C / min, keeping warm for 6 hours, and then naturally cooling to room temperature with the furnace to prepare the LATP oxide solid electrolyte sheet.
[0077] The LATP oxide solid electrolyte sheet prepared in this comparative example was characterized and analyzed, and its XRD diffraction pattern is as follows: Figure 1 As shown in the SEM images Figure 4 As shown, the EIS spectrum is Figure 7 shown.
[0078] pass Figure 1 It can be seen that the peak position of the LATP oxide solid electrolyte sheet prepared in this comparative example is completely consistent with that of the standard card, and it is pure phase LATP without obvious impurity peaks.
[0079] pass Figure 4 It can be seen that the LATP oxide solid electrolyte sheet prepared in this comparative example has uniform grain size, but compared with the LATP oxide solid electrolyte sheet prepared in Example 1, it has obvious gaps and poor density.
[0080] based on Figure 7 After fitting and calculation, the ionic conductivity of the LATP oxide solid electrolyte sheet prepared in this comparative example is 7.40×10 -5 S / cm, compared with Example 1, is significantly reduced.
[0081] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for rapidly densifying a solid oxide electrolyte for lithium-ion batteries, characterized in that: The preparation method comprises the following steps: (1) Forming an oxide solid electrolyte powder into a tablet to prepare an oxide solid electrolyte green body, wherein the oxide solid electrolyte powder is Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder or Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Solid electrolyte powder, the Li 1.4 Al 0.4 Ti 1.6 (PO4)3 solid electrolyte powder is used to prepare LATP green body. 6.4 Ln3Z 1.4 Ta 0.6 O 12 The solid electrolyte powder was used to prepare the LLZTO green body; (2) The LATP green body or the LLZTO green body is placed between conductive substrates, and the conductive substrates are electrified to generate Joule heat to act on the green body for sintering, and a two-stage heating method is performed: the first stage is a preliminary densification sintering at 400-700°C, and the constant temperature time is 3-30s; the second stage is a further densification sintering at 900-1200°C, and the constant temperature time is 1-10s to obtain an oxide solid electrolyte sheet. The sintering needs to be carried out in a protective atmosphere, and the protective atmosphere is one of air and oxygen. The oxide solid electrolyte sheet is a LATP electrolyte sheet or a LLZTO electrolyte sheet.
2. The method for rapidly densifying a solid oxide electrolyte for lithium ion batteries according to claim 1, characterized in that: In the step (1), the tableting pressure is 2-8 MPa, and the holding time is 1-3 min.
3. The method for rapidly densifying a lithium ion battery oxide solid electrolyte according to claim 1, characterized in that: In the step (1), the oxide solid electrolyte green body is a circular sheet with a diameter of 12-18 mm and a thickness of 0.5-2 mm.
4. A method for rapidly densifying a solid oxide electrolyte for lithium ion batteries according to claim 1 or 3, characterized in that: In the step (2), the conductive substrate is one of nickel foil, copper foil, aluminum foil, carbon cloth, carbon felt, carbon fiber, and graphite crucible.
5. The method for rapidly densifying a solid oxide electrolyte for lithium ion batteries according to claim 4, characterized in that: The conductive substrate is a rectangular structure, and the width of the conductive substrate is 1 to 3 times the diameter of the oxide solid electrolyte green body.
6. A method for rapidly densifying a solid oxide electrolyte for lithium ion batteries according to any one of claims 1, 2, 3 and 5, characterized in that: In the step (2), the ionic conductivity of the prepared oxide solid electrolyte sheet is greater than or equal to 2.0×10 -4 S / cm, the density is greater than or equal to 97%, and the electrochemical stability window is 0~6V.
Citation Information
Patent Citations
High-toughness oxide solid electrolyte as well as preparation method and application thereof
CN114725488A